The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1513/annalsats.201904-344ws
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health after Military Service in Southwest Asia and Afghanistan. An Official American Thoracic Society Workshop Report

Abstract: Since 2001, more than 2.7 million U.S. military personnel have been deployed in support of operations in Southwest Asia and Afghanistan. Land-based personnel experienced elevated exposures to particulate matter and other inhalational exposures from multiple sources, including desert dust, burn pit combustion, and other industrial, mobile, or military sources. A workshop conducted at the 2018 American Thoracic Society International Conference had the goals of: 1 ) identifying key studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 110 publications
1
36
0
Order By: Relevance
“…Despite the uncertainty in the medical literature, unexplained respiratory symptoms occurring in soldiers deployed to Southwest Asia has been well described. [1][2][3][4] It has also been recognised that landbased personnel deployed to countries in Southwest and Central Asia, such as Iraq, Afghanistan, Kuwait, Qatar and the United Arab Emirates, may have been exposed to harmful particulate matter and respiratory pollutants. 3 However, there has been a paucity of data defining the histological features behind these pulmonary symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the uncertainty in the medical literature, unexplained respiratory symptoms occurring in soldiers deployed to Southwest Asia has been well described. [1][2][3][4] It has also been recognised that landbased personnel deployed to countries in Southwest and Central Asia, such as Iraq, Afghanistan, Kuwait, Qatar and the United Arab Emirates, may have been exposed to harmful particulate matter and respiratory pollutants. 3 However, there has been a paucity of data defining the histological features behind these pulmonary symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] It has also been recognised that landbased personnel deployed to countries in Southwest and Central Asia, such as Iraq, Afghanistan, Kuwait, Qatar and the United Arab Emirates, may have been exposed to harmful particulate matter and respiratory pollutants. 3 However, there has been a paucity of data defining the histological features behind these pulmonary symptoms. This is explained as being due primarily to the low frequency of lung biopsies in clinical studies regarding deployed personnel, and therefore the ability to study histological findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sources included open-air waste burning (burn pits) at bases, desert dust, vehicle exhaust, military operations, and poorly regulated local industrial sources. 1 Sampling in deployment areas indicated elevated 24-h PM 2.5 (PM # 2.5 mm in diameter) mean annual values (~40 mg/m 3 to nearly 120 mg/m 3 ). 2 Other studies have also identified levels far exceeding the US ambient annual PM 2.5 standard of 12 mg/m 3 .…”
mentioning
confidence: 95%